Screening of native Saccharomyces cerevisiae strains from Chile for beer production - Moreira-Ramos, Sandra; Saavedra-Torrico, Jorge; G-Poblete, Camila; Godoy Olivares, Liliana; Sangorrin, Marcela; Ganga, María Angélica (Frontiers in Microbiology, 2024)
Beer is one of the most consumed alcoholic drinks in the world, and this industry is a growing market that demands different properties to satisfy new consumers. The yeasts are used in different fermented beverages to contribute to new flavors. However, yeast strains used in the beer industry are limited so far, thus the diversity of flavors is very restricted. Therefore, the use of native yeast strains has been taking more importance with the purpose of conferring differentiated organoleptic properties to the product. Based on this observation the potentiality of native Saccharomyces cerevisiae strains obtained from different localities in Chile was researched. Then, were selected those strains that produced the highest ethanol concentration (nearly 6% v/v), consumed the highest amounts of sugars, and produced the lowest amounts of organic acids in the resulting beers. Finally, we did a beer tasting to select those strains that added different flavors to the final beer compared with a commercial strain used. In this study, two native strains that produced fruity descriptors are described, which could be used in the future in brewing, craft or industrial production.